The Incidence of Hypertension of Posbindu PTM Participants - Siti Khoiriyah; Abdullah Azam Mustajab (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Non-communicable diseases cannot be transmitted to others, but their development occurs slowly over a long period of time. One of the non-communicable diseases that is a priority in global health today is hypertension. Hypertension often causes complications such as stroke, heart disease, and kidney failure. The aim is to describe the incidence of hypertension in Posbindu PTM Bumiroso participants. The quantitative descriptive method using the total sampling technique obtained 38 respondents. The data was analyzed descriptively to describe the results of the respondents' blood pressure examinations. The results of the study based on the classification of hypertension, participants who experienced pre-hypertension and hypertension level 1 were 12 (31.58%), hypertension level 2 was 9 (23.68%) and normal was 5 (12.16%). The conclusion is that more than half of Posbindu PTM participants experience hypertension, as a suggestion, they can carry out routine checks at the nearest health facility.